Penerapan Model Pembelajaran Inquiry Berbantuan Simulasi PhET untuk Meningkatkan Literasi Sains Peserta Didik Kelas XII - Solehayati, Rasna; Kariadinata, Rahayu; Chusni, Muhammad Minan (Alpatih Harapan Semesta, 2025)
This study aims to examine the improvement of students’ scientific literacy through the implementation of the inquiry learning model supported by PhET simulation on capacitor material. The background of this research is the low ability of students to understand capacitors conceptually and applicatively. This experimental study used a Pre-Experimental Design with one experimental class consisting of 34 Grade XII students at SMA Karya Pembangunan 1 Ciparay in the 2025/2026 academic year. Data were collected using pre- and post-scientific literacy tests. The results showed an average N-Gain score of 0.38 (medium category) with an effectiveness percentage of 37.38% (ineffective interpretation). A Paired Samples Test revealed a significant difference between pretest and posttest scores, with an improvement of 23.73 points, t(33)=7.381, p<0.001. These findings indicate that inquiry learning with PhET simulation significantly enhances scientific literacy, although its implementation has not yet reached effective criteria. Implication suggests further integration of laboratory activities and teacher guidance. Researchers recommend optimizing digital scaffolding and training for teachers.